Multi-scale study of the deformation mechanisms of thermoelectric p-type half-Heusler Hf0.44Zr0.44Ti0.12CoSb0.8Sn0.2 - Aumand, Matthieu; Amiard, Guillaume; He, Ran; Ren, Zhifeng; White, Ken W.; Thilly, Ludovic (Journal of applied physics, 2018)
Increasing the figure of merit ZT of thermoelectric (TE) alloys is a challenge that is currently attempted through various metallurgy methods, including nanostructuring and dislocation engineering. Microstructures with such a level of complexity raise questions about the mechanical reliability of these new materials. Indeed, despite the values of hardness and elastic modulus known for the clear majority of TE materials, the data on deformation mechanisms are still rare. Focusing on the nanostructured p-type half-Heusler Hf0.44Zr0.44Ti0.12CoSb0.8Sn0.2, our multi-scale study aims to analyze the deformation mechanisms. Experiments conducted at macro-, meso-, and micro-scale are designed to trigger and assess plasticity mechanisms. Compression testing on bulk samples subject to a confining pressure environment and temperature leads to an exclusive brittle failure. The mixed-mode failure mechanisms involve switching between intra- and inter-granular crack propagation, depending on the grain size met by the crack tip. Cube-corner nanoindentation at meso-scale generates cracks and enables fracture toughness estimation, while TEM analysis of the crack tip area confirms no dislocation activity and 3D-Electron Back Scattered Diffraction technique confirms the mixed crack propagation behavior. At micro-scale, micro-pillar compression stress-strain curves and failure mechanisms are comparable with bulk samples testing analysis. These results can be used to provide design guidelines for more crack-resistant TE alloys.